ELECTRONIC CERTIFICATES OF LAND RIGHTS AND THE CONCEPT OF IMMUTABILITY IN INDONESIAN NATIONAL LAND LAW: ELECTRONIC CERTIFICATES OF LAND RIGHTS AND THE CONCEPT OF IMMUTABILITY IN INDONESIAN NATIONAL LAND LAW - Rahmat, Rahmat; Irianto, Agung; Hidayati, Mashlihati Nur; Nut, Nut (PENA LAW: International Journal of Law, 2025)
Digital transformation in the land sector has led to the implementation of electronic certificates as an effort to modernize national land administration. In this system, the principle of immutability, or the unchangeability of data after it has been recorded, is an important basis for ensuring the integrity and validity of land rights data. This paper analyses the relevance of the concept of immutability in information technology to the electronic certificate system from the perspective of national land law. Through a normative juridical approach and a study of legislation, it is found that while the principle of immutability enhances legal protection, data validity, and service efficiency, it remains subject to basic principles of land law that allow for the annulment of rights on the basis of legal decisions. The study recommends strengthening technical and legal regulations and developing blockchain-based systems to support the immutability principle in land administration. The concept of immutability in law is closely related to the principle of legal certainty. In the context of Indonesian national land law, this concept is reflected in the land registration system that gives legal force to registered land rights. This article discusses the relationship between legal theories and the concept of immutability, as well as its application in national land law, particularly through the Basic Agrarian Law (UUPA) and Government Regulation No. 24 of 1997 on Land Registration. The study shows that the principle of immutability is the foundation for ensuring stability, legal security and protection of land rights.